Pengaruh Return On Equity, Earnings Per Share, Economic Value Added, Dan Market Value Added Terhadap Return Saham Perusahaan Sektor Pertanian Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2016 - Nastasya Cindy Hidajat (Jurnal Ekonomi, 2018)
The purpose of this research was to test the effect of return on equity, earning per share, economic value-added, and market value added to stock return of agriculture firm that listed at Indonesian Stock Exchange in the period of 2010-2016 either partially or simultaneously. This research used 77 samples. The method used is panel data regression analysis using EViews 6. The results showed that return on equity, earning per share economic value added, and market value added partially has positive significant influence on the stock return, and return on equity, earning per share, economic value added, and market value added simultaneously affect the stock return.